Population pharmacokinetics and model-informed precision dosing of lamivudine in Chinese HIV-infected patients with mild and moderate impaired renal function. Issue 5 (4th May 2022) - Wen, Haini; Yin, Lin; Wang, Jiangrong; Zhang, Lin; Sun, Tao; Xu, Feng; Zhang, Minxin; Liu, Li; Zhang, Renfang; Liu, Xiaoqian; Meng, Xianmin; Xing, Yaru; et al.
ABSTRACT: Background: Lamivudine is a first-line medication used for human immunodeficiency virus (HIV) treatment. To date, the population pharmacokinetics of lamivudine in Chinese HIV-infected adults have not been assessed. This study aimed to develop a population pharmacokinetic model for oral lamivudine in Chinese HIV-infected adults and to determine the optimal lamivudine dosage regimens. Research design and methods: A total of 1113 samples, from 828 Chinese HIV-infected patients treated with lamivudine 300 mg every 24 hours, were pooled from two open-label, prospective clinical trials. A population pharmacokinetics analysis was performed using a nonlinear mixed-effects modeling method. A Monte Carlo simulation was conducted to optimize lamivudine dosing. Results: A two-compartment model adequately described the population pharmacokinetics of lamivudine. The typical population estimate for apparent clearance was 28.3 L/h. Creatinine clearance was identified as a significant factor influencing apparent clearance. According to the Monte Carlo simulation, patients with creatinine clearance between 50 and 70 mL/min should receive lamivudine 200 mg every 24 h or 300 mg every 36 h, to achieve optimal lamivudine exposure. Conclusions: No obvious ethnic differences were observed in lamivudine pharmacokinetics between Chinese and Caucasian populations. Additionally, a model-informed dosage regimen is recommended for patients with impaired renal function.